Capnographic monitoring of propofol-based sedation during colonoscopy - Friedrich-Rust, Mireen; Welte, Maria; Welte, Carmen; Albert, Joerg; Meckbach, Yvonne; Herrmann, Eva; Kannengiesser, Matthias; Trojan, Joerg; Filmann, Natalie; Schroeter, Hartmut; Zeuzem, Stefan; Bojunga, Joerg (Endoscopy, 2014)
Background and study aims: Capnography enables the measurement of end-tidal CO2 and thereby the early detection of apnea, prompting immediate intervention to restore ventilation. Studies have shown that capnographic monitoring is associated with a reduction of hypoxemia during sedation for endoscopy and early detection of apnea during sedation for colonoscopy. The primary aim of this prospective randomized study was to evaluate whether capnographic monitoring without tracheal intubation reduces hypoxemia during propofol-based sedation in patients undergoing colonoscopy.Patients and methods: A total of 533 patients presenting for colonoscopy at two study sites were randomized to either standard monitoring (n = 266) or to standard monitoring with capnography (n = 267). The incidence of hypoxemia (SO2 < 90 %) and severe hypoxemia (SO2 < 85 %) were compared between the groups. Furthermore, risk factors for hypoxemia were evaluated, and sedation performed by anesthesiologists was compared with nurse-administered propofol sedation (NAPS) or endoscopist-directed sedation (EDS).Results: The incidence of hypoxemia was significantly lower in patients with capnography monitoring compared with those receiving standard monitoring (18 % vs. 32 %; P  = 0.00091). Independent risk factors for hypoxemia were age (P = 0.00015), high body mass index (P = 0.0044), history of sleep apnea (P = 0.025), standard monitoring group (P = 0.000069), total dose of propofol (P = 0.031), and dose of ketamine (P < 0.000001). Patients receiving anesthesiologist-administered sedation developed hypoxemic events more often than those receiving NAPS or EDS. In patients with anesthesiologist-administered sedation, sedation was deeper, a combination of sedative medication (propofol, midazolam and/or ketamine) was administered significantly more often, and sedative doses were significantly higher compared with patients receiving NAPS or EDS. Conclusions: In patients undergoing colonoscopy during propofol-based sedation capnography monitoring with a simple and inexpensive device reduced the incidence of hypoxemia.